Philosophical intuitionism and literary stylistics - Vilariño Picos, M.ª Teresa (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
The concern shown by literary stylistics for the specific nature of works of art goes beyond the limits of literary criticism. This concern, in fact, approaches a critical, theoretical consideration. Likewise, its aim to be considered as a science of literature because of, precisely, the aesthetic dimension of literary fact, inclines it to employ the method of the philosophical intuition, which is a unique model that provides it with the necessary precision and rigour, to be the cardinal support of most of its analyses. In this sense, the interaction between the two cultural fields, the philosophical and the literary, can be seen in the work of the most outstanding representatives of the literary side of the stylistic movement: Benedelto Croce, Karl Vossler and Leo Spitzer, as well as Amado Alonso and Dámaso Alonso. All of them without exception, make use, to a greater or lesser extent, of the different shades that this concept of philosophical intuition acquires, on one hand in the figure of Henri Bergson, and on the other hand, in Edmund Husserl, for the conformation of its theoretical foundations.
Keywords: Stylistics; philosophical intuition